2020
DOI: 10.1111/jfpp.15093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bran addition on rheological properties of dough and quality of triticale bread

Abstract: The purpose of this study was to examine the effects of the addition of triticale bran on the production of triticale bread. This work assessed in detail the properties of the dough and the quality of the bread with added bran, which was obtained from the grain of two selected triticale cultivars: Fredro and Panteon. The results showed that flours of these cultivars were suitable for bread‐making. The addition of bran to baking blends positively affected the rheological properties of the dough and led to a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The triticale flour and bran obtained from tested cultivars enables the production of good-quality bread, which is also confirmed by other authors [ 6 , 7 , 32 ]. In our study, the products such as flour, bran, and breads, obtained from the grain of tested triticale cultivars were analyzed of the contents of PAs ( Table 3 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The triticale flour and bran obtained from tested cultivars enables the production of good-quality bread, which is also confirmed by other authors [ 6 , 7 , 32 ]. In our study, the products such as flour, bran, and breads, obtained from the grain of tested triticale cultivars were analyzed of the contents of PAs ( Table 3 ).…”
Section: Resultssupporting
confidence: 87%
“…The search for new ideas, for example, the development of new products based on cereals and their preserves, enables growth in the offer of cereal products with pro-health properties [ 33 ]. In view of the above, triticale flour may be the raw material for their production [ 6 , 32 , 33 ]. In our experiment, triticale bread with added bran, which could be included in the daily diet, was baked and examined for the content of PAs.…”
Section: Resultsmentioning
confidence: 99%
“…These results also showed that the lower protein content could cause shorter development time and the higher total and SDF content accompanied by higher water absorption value and longer development time. This suggests that fibre content, composition and the properties of components (water solubility, molecular size and structure) may play a major role in the development of mixing properties of rye flours and especially fractions (Sanz Penella et al ., 2008; Kaszuba et al ., 2021). It was found that the paste viscosity of fractions with higher fibre content was lower in most cases than previously described (Aprodu & Banu, 2016; Deleu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The use of triticale flour as a raw material in the place of wheat flour is promising. This flour can be used to create a variety of food and beverage products including bread [12], cookies [4], pasta [13], malt [14] cereal bars [15], ethanol [16] and edible films [17].…”
Section: Introductionmentioning
confidence: 99%